Constipation in elderly woman participants of a health promotion program in Santa Maria (RS): Prevalence, symptoms and psychosocial factors associated - Braz, Melissa Medeiros (2015)
This paper aims to investigate the prevalence and characteristics from diverse kind of constipation among older women. It is an observational study, where 50 elderly women over the age of 60 years were interviewed. From this study, we observed a high prevalence of constipation, when the most frequently reported symptoms were incomplete evacuation (58%) and the sensation of anorectal obstruction (46%). These data indicate the importance of caring for these women, in order to avoid discomforts resulting in daily life, impairing their quality of life.